Visual Challenges in the Everyday Lives of Blind People - Brady, Erin; Morris, Meredith Ringel; Zhong, Yu; White, Samuel; Bigham, Jeffrey P. (Proceedings of CHI 2013, 2013)
The challenges faced by blind people in their everyday lives are not well understood. In this paper, we report on the findings of a large-scale study of the visual questions that blind people would like to have answered. As part of this yearlong study, 5,329 blind users asked 40,748 questions about photographs that they took from their iPhones using an application called VizWiz Social. We present a taxonomy of the types of questions asked, report on a number of features of the questions and accompanying photographs, and discuss how individuals changed how they used VizWiz Social over time. These results improve our understanding of the problems blind people face, and may help motivate new projects more accurately targeted to help blind people live more independently in their everyday lives.